Comparison of Two School Feeding Programmes in Ghana, West Africa - Owusu, Justina S.; Colecraft, Esi K.; Aryeetey, Richmond N.O.; Vaccaro, Joan A.; Huffman, Fatma G. (International Journal of Child Health and Nutrition, 2016)
Background: Malnutrition of children in Ghana continues during school years. There is limited information on how school meals meet nutrient recommendations in Ghana. Objectives: The aim of this study was to compare energy and nutrient content of meals served by Ghana School Feeding Programme (GSFP) and Non-Governmental School Feeding Programme (NGSFP) and adherence to nutrient recommendations. Methods: This was a cross sectional study design involving observation of school meals at two sites: GSFP and NGSFP. Average weights of a week’s meal were converted to energy and nutrient equivalence and compared with international recommendations. Differences assessed with t-tests. Results: NGSFP provided significantly higher portion size (416 ± 96 g vs. 243 ± 50 g; p=0.007), energy (776 ± 427 kcal vs. 315 ± 24 kcal; p=0.042) and fats (17± 8 vs. 6 ± 2; p=0.019) but similar micronutrient contributions to GSFP. NGSFP met energy and macronutrient recommendation set by World Food Programme; whereas, GSFP did not meet the recommendations. Conclusion and Recommendations: The NGSFP had more energy and macronutrients per serving size than the GSFP. Regulation of meals served by GSFP should be reviewed to ensure they contribute to the adequacy of children’s diets as well as meet recommendations set by World Food Programme.